Research trends on interventional studies for Mild Cognitive Impairment (MCI): A bibliometric analysis using CiteSpace. - Karim, Mani Abdul; Venkatachalam, Jonnadula (Ageing International, 2025)
Background: Mild Cognitive Impairment (MCI) is a transitional stage between normal aging and the onset of dementia. The early detection of MCI is essential to avoid certain irreversible brain damage at the end of life. While there have been a variety of preventive interventions used in the past three decades, need to know the current trends is necessary for developing updated preventive modules for MCI. Objectives: This bibliometric study examines the current trends in interventional research for treating MCI. Methods: Published records were obtained from the Web of Science Core Collection (WoSCC) for the period of 1989–2023. CiteSpace 6.2.R4 (64-bit) advanced version software was utilized for mapping and bibliometric analysis of this study. Overall, 400 records were retrieved and analyzed using document co-citation analysis (DCA), author co-citation analysis (ACA), institutional, country based, and keyword analysis. Results: It was found that the publication records were steadily increased in the recent five years (2018–2022) and shows that more than half of the interventional studies (234) were conducted on the recent times. Although United States (US) published highest number of publications (115), Canada secured top position based on burst (3.89) in country wise analysis. In ACA, Petersen RC_2003 secured top position based on citation counts (237), Rapp S_2006 on Burst strength (10.69), Ball K_2006 on Centrality (0.19) and Sigma value (2.00). Through the DCA analysis, clusters such as computerized cognitive training, virtual reality, rhythm training, and dance intervention, were considered to be the indicators of emerging trends.